Response of broiler chickens to dietary inclusion of fermented canola meal under heat stress condition - Aljubori, Ahmed; Idrus, Zulkifli; Soleimani, Abdoreza Farjam; Abdullah, Norhani; Liang, Juan Boo (Taylor & Francis Group, 2017)
Feeding high levels of canola meal to monogastric animal require reducing antinutritional factors such as glucosinolates and fibre. Solid state fermentation is known to reduce antinutritional factors and improve nutritional quality of feedstuffs. In this study, canola meal was treated with Lactobacillus salivarius in solid state fermentation for 30 days and included in diet with 4 levels of 0 (control), 10, 20, and 30%. From 29 to 35 days of age, equal number of birds from each dietary treatment was exposed to either 23 ± 1 °C (unheated) or 36 ± 1 °C (heated). Results showed that irrespective of temperature, weight gain (WG) and feed conversion ratios (FCR) were not affected by inclusion of fermented canola meal (FCM). Diet also did not affect carcass yield, plasma triiodothyronine (T3) and tetraiodothyronine (T4), and body temperature. As expected, heated birds had lower carcass yield and T3 than their unheated counterparts. In conclusion, although dietary inclusion of FCM at levels more than 10% retarded growth performance during 1 to 28 days of age, no detrimental effects on performance was observed when FCM included up to 30% during 29 to 35 days of age under both unheated and heated conditions.